Direct penetration of spin-triplet superconductivity into a ferromagnet in Au/SrRuO3/Sr2RuO4 junctions - M. S. Anwar (Nature Portfolio, 2016)
The injection of spin-polarized supercurrent into a ferromagnet presents the possibility of zero-resistance spintronic devices. Here, the authors evidence the direct injection of spin polarized supercurrent into ferromagnetic SrRuO3 from a candidate spin-triplet superconductor Sr2RuO4.